Ocena działalności Wielkopolskiego Oddziału Agencji Restrukturyzacji i Modernizacji Rolnictwa w ramach Działania 3 programu operacyjnego SAPARD dla Polski - Sierszchulski, Jarosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
The aim of the paper was the attempt of evaluation of activity of Agency for Restructuring and Modernization of Agriculture based on Structural Pre-accession Measure for Agriculture and Rural Development. The problem was worked out on the basis of data received from original sources like a postal or electronic poll as well as derivative sources like acts or reports of Agency. The poll was carried out in April 2003. The research included 226 communes of Wielkopolska Province. Only 62 communes replied. As a result of the research some information was obtained: estimation of technical infrastructure, needs and planned investments in this area, access to information about support programs, communes' activity in taking advantage of European Union finances, communes' cooperation with the Agency. As a result of the research there were shown the directions of activities which are essential for increasing in absorption of European finances by the communes. There was prepared the project of rationalizations increasing possibilities of using European Fund in analyzed sector.